Mapping the stacking interaction of triphenyl vinylene oligomers with graphene and carbon nanotubes. (January 2019) - Yaya, A.; Impellizzeri, A.; Massuyeau, F.; Duvail, J.L.; Briddon, P.; Ewels, C.P.
Abstract: Using density functional calculations, we explore π-π and π -H stacking interactions in conjugated polymer – carbon nanomaterial composites, through a detailed surface energy mapping procedure. Taking the triphenyl vinylene oligomer as a structural model for poly para-phenylene vinylene (PPV), we map intermolecular stacking configurations between PPV pairs. We then map PPV translation over the surface of graphene, and explore orientation dependence in PPV-nanotube interaction with tubes of different chirality and diameter. Preferential stacking orientations are shown, and commensurability between the polymer and carbon substrate is demonstrated. Conjugated polymers such as PPV lie at the crossroads between small organic molecules such as benzene and extended conjugated carbon systems such as graphene. With the current calculations we are able to reconcile the range of stacking behaviours seen in these diverse materials, with literature experimental polarized Raman spectroscopy results. Graphical abstract: Image 1